Morphological Study of the Heart of the Indonesian Short-Nosed Fruit Bat (Cynopterus titthaecheilus) - Anisa Rahma; Desrayni Hanadhita; Andhika Yudha Prawira; SUPRATIKNO KASMONO; HERA MAHESHWARI; Aryani Sismin Satyanintijas; Srihadi Agungpriyono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rahma A, Hanadhita D, Prawira AY, Kasmono S, Maheshwari H, Satyaningtijas AS, Agungpriyono S. 2020. Morphological study of the heart of the Indonesian short-nosed fruit bat (Cynopterus titthaecheilus Temminck, 1825). Biodiversitas 21: 5094-5101. The energy demand of an animal becomes an important factor that affects the adaptation of cardiac or heart anatomy. As the largest Cynopterus bat in Indonesia, Cynopterus titthaecheilus (Temminck, 1825) is one of the flying mammals that need a lot of energy to accommodate its flying activity. This study aims to acknowledge the anatomical adaptation of the heart in C.titthaecheilus, which includes the weight ratio of the heart, heart structure, and primary blood vessel branches. This study conducted of 10 juvenile C. titthaecheilus (56.15±13.43 g), 13 females (74.38±10.34 g), and 18 males (73.27±13.54 g). Bats ware killed by ketamine overdoses, then the thoracic cavity was opened and the heart was removed from the thoracic cavity for observation. The results of this study revealed that the ratio of heart mass to body mass of adult female C. titthaecheilus was 0.014, male adult C. titthaecheilus was 0.015 and juvenile C. titthaecheilus was 0.015. The heart-shaped was an oval, located in the thoracic cavity, tilted to the left. On the other hand, the heart structure of C. titthaecheilus consisted of a thicker left ventricle compared to the right ventricle, but the musculi pectinati, musculus papillaris, and trabecula septomarginalis were well developed on the right side of the heart compared to the left side. Subsequently, the branches of the primary blood vessels in the heart consisted of an aortae ascendens, three arteria pulmonalis dextra and one arteria pulmonalis sinistra, a vena pulmonalis, the vena cava anterior dextra et sinistra, and a single vena cava posterior. In addition, the conus arteriosus, which is an enlarged space of the pulmonary artery, was observed in a large size. Based on this study, it was concluded that the heart structure of C. titthaecheilus was very important in supporting their ability to fly.